Multiple Sclerosis-Related Dietary and Nutritional Issues: An Updated Scoping Review with a Focus on Pediatrics - Claudia Mandato; Angelo Colucci; Roberta Lanzillo; Annamaria Staiano; Elena Scarpato; Luigi Schiavo; Francesca Felicia Operto; Maria Rosaria Serra; Cristina Di Monaco; Julia Sara Napoli; Grazia Massa; Pietro Vajro (MDPI AG, 2023)
Purpose. Lifestyle/dietetic habits play an important role in the development and progression of multiple sclerosis (MS) disease. Here, we examine the basic pathomechanisms underlying intestinal and brain barrier modifications in MS and consider diets and dietary supplementations proposed over time to complement pharmacological therapies for improving disease outcome both in adults and in children. Methods. Scoping literature search about evidence-based findings in MS-related gut-brain axis (GBA) pathophysiology and nutritional issues at all ages. Findings. Data show that (1) no universal best diet exists, (2) healthy/balanced diets are, however, necessary to safeguard the adequate intake of all essential nutrients, (3) diets with high intakes of fruits, vegetables, whole grains, and lean proteins that limit processed foods, sugar, and saturated fat appear beneficial for their antioxidant and anti-inflammatory properties and their ability to shape a gut microbiota that respects the gut and brain barriers, (4) obesity may trigger MS onset and/or its less favorable course, especially in pediatric-onset MS. Vitamin D and polyunsaturated fatty acids are the most studied supplements for reducing MS-associated inflammation. Conclusions. Pending results from other and/or newer approaches targeting the GBA (e.g., pre- and probiotics, engineered probiotics, fecal-microbiota transplantation), accurate counseling in choosing adequate diet and maintaining physical activity remains recommended for MS prevention and management both in adults and children.